PENGEMBANGAN ALAT UKUR KUALITAS HIDUP NELAYAN - Antonia Junianty Laratmase (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2016)
ABSTRACT The purpose of the study to see how to the measure quality of life. This analysis quality of life of fisherman at Karawang, because fishermen’s at the Karawang need attention. The objective of this research is the development of instruments in measuring fishermen’s quality of life: An approach study factor analysis in construct validity testing.This research was conducted in Desa Cilamaya Kabupaten Karawang. The methodology the writer uses quantitative. The sample sizes of this research are 40 fishermen. The data was compiled from questionnaire list and was analyzed using descriptive data and factor analysis techniques. The data analysis and interpretation two dimension objective and existential of quality of life. The result of the research shows to measurement Fishermen’s quality of life that have two dimensioned objective and existential. So this here quality of life can be measure and then harmony and ability that is the integrated of quality of life.